Media, The new laboratory for the public opinion industry "Analytical sociological study" - دلالة, ميرنا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The current research aims to clarify and discuss the profound change that has occurred on the knowledge map in the field of media due to the development of communication and media technology. This is something produced by a new wave of existing thinking about the influence of "effective" social networks in creating and directing public opinion. Therefore, in this research we will try to discuss the idea that the power of influence enjoyed by social networks is from a sociological point of view an overlook of the human role and the technology that constitutes the reality of events. Events may not be created, directed or led by communication and media technology, as much as they are the product of a complex web of human-technical interactions. Therefore, in our current research, we will rely on a theoretical approach through which we can reveal the power of the media as the new laboratory for public opinion industry.